IMPLEMENTASI PENJUALAN ONLINE PADA CV. MAHKOTA JATI DENGAN METODE QUICK SORT - Noor Santi, Rina Candra; Buwana, Aditya Kusuma (Information Technology and Telematics, 2019)
Abstract- E-commerce is promising enough to be implemented at this time, because e-commerce provides a lot of convenience for both parties both from the CV. Mahkota Jati and from customers. To facilitate the search and sorting of items in an e-commerce method, sorting is used quick sort.The system development method used in this study is waterfall which consists of requirements definition, system and software design with UML, implementation using PHP and MySQL.The final result of this research is with using e-commerce CV. Mahkota Jati can increase sales of goods at CV. Mahkota Jati, making it easier for customers to find CV products. Mahkota Jati, displaying from the lowest prices of furniture to furniture with the highest prices